Trends in HIV testing in the UK primary care setting: a 15-year retrospective cohort study from 2000 to 2015 - Gompels, Mark; Michael, Skevi; Davies, Charlotte; Jones, Tim; Macleod, John; May, Margaret (BMJ open, 2019)
ObjectivesTo estimate trends in HIV testing, positivity and prevalence in UK primary care for 2000–2015 as part of a wider investigation into reasons for late diagnosis of HIV.DesignRetrospective cohort study using the Clinical Practice Research Datalink (CPRD) which is derived from computerised clinical records produced during consultations in primary care.Setting404 general practices in England.Participants5 979 598 adults aged ≥16 years registered between 2000 and 2015 with 45 093 761 person years of observation.OutcomesAnnual HIV testing rates, proportion of positive tests and prevalence of HIV-infected people recorded in primary care 2000–2015.ResultsHIV testing in primary care increased from 2000 to 2010, but then declined. Testing was higher in females than in males and in those aged 16–44 years compared with older adults. Rates per 100 000 in women aged 16–44 years were 177 (95% CI 167 to 188); 1309 (95% CI 1282 to 1336); 1789 (95% CI 1757 to 1821) and 839 (95% CI 817 to 862) in 2000, 2005, 2010 and 2015, respectively, and for non-pregnant women: 22.5 (95% CI 19 to 26); 134 (95% CI 125 to 143); 262 (95% CI 250 to 275); 190 (95% CI 179 to 201). For men aged 16–44 years rates were: 26 (95% CI 22 to 29); 107 (95% CI 100 to 115); 196 (95% CI 185 to 206); 137 (95% CI 127 to 146). Over the study period, there were approximately two positive results per 1000 HIV tests. Men were eightfold more likely to test positive than women. The percentage of HIV diagnoses among adults recorded in CPRD may be as low as 55% in London and 67% in the rest of the UK.ConclusionsHIV testing rates in primary care peaked in 2010 and subsequently declined. Access to testing was higher for women despite the prevalence of HIV being higher in men.Implications and further research neededOpportunities remain in primary care for increasing HIV testing to prevent costly late diagnoses and decrease HIV transmission. Interventions to improve targeting of tests and increase adherence to HIV testing guidelines are needed in primary care.